Donor-recipient Sex Differences Do Not Affect Survival Outcomes After Kidney Transplantation: A Population Cohort Study. Issue 5 (May 2020) - Morgan, Georgia; Goolam-Mahomed, Zahrah; Hodson, James; Nath, Jay; Sharif, Adnan
Abstract : Background: Donor factors can influence decision making for organ utilization for potential kidney transplant candidates. Prior studies exploring the effect of donor-recipient sex matching on kidney transplant outcomes have reported heterogenous and conflicting results. The aim of this contemporary population-cohort analysis was to explore the effect of donor-recipient sex matching on kidney transplant outcomes in the United Kingdom. Methods: In this retrospective, observational study, we analyzed all patients receiving kidney-alone transplants between 2003 and 2018 using UK Transplant Registry data. Stratified by recipient sex, outcomes were compared between male and female donors with univariable/multivariable analyses. Results: Data were analyzed for 25 140 recipients. Of these, 13 414 (53.4%) of kidneys were from male donors and 15 690 (62.4%) of recipients were male. The odds of initial graft dysfunction (delayed graft function/primary nonfunction) were significantly lower for female donor kidneys transplanted into both male (adjusted odds ratio = 0.89, 95% confidence interval [CI] = 0.80-0.98, P = 0.019) and female (adjusted odds ratio = 0.81, 95% CI = 0.71-0.93, P = 0.003) recipients. Male recipients of female donor kidneys had creatinine levels at 1 year that were 6.3% higher (95% CI = 4.8%-7.7%, P < 0.001) than male recipients of male donor kidneys, with a similar sex difference of 4.1% (95% CI = 2.1%-6.1%, P < 0.001) observed within female recipients. However, neither patient nor graft survival was found to differ significantly by donor sex on either univariable or multivariable analysis. Conclusions: Our data provide contemporary data on sex mismatch for recipient counseling and reassurance with regards to equivalent long-term clinical outcomes based upon donor sex. Abstract : Supplemental Digital Content is available in the text.